Logistics development in Malaysia East Coast Region: infrastructure, constraints and challenges - Zuraimi Abdul Aziz; Mohd Rafi Yaacob; Mohamed Dahlan Ibrahim (2013)
This paper examines the current logistics development in the East Coast Region of Peninsular Malaysia. Malaysia as well as other developing countries are still at the moderate stage in developing logistics systems and often face considerable challenges and constraints to provide efficient and effective logistics service. This research is based on survey conducted in the region. The respondents were from the different logistics players and stakeholders. Altogether there were 41 usable questionnaires were analyzed. In general the results reveal logistic players satisfied with the current logistics infrastructures in the region. However, further analysis found organizations that have been operated more than 10 years neither satisfied nor dissatisfied with the current logistics infrastructures. In addition this study found a couple of constraints and challenges in the logistics industry and amongst them were professionalism in supporting the development, skill of manpower and financial issues within organizations deal with logistics.